Gandhi's ascetic activism : renunciation and social action - Howard, Veena R. (Albany : State University of New York Press, 2013)
In this book, the author discusses Gandhi's creative use of ascetic practice, particularly his practice of celibacy, for nonviolent activism.
Notes on Symbols from Indian Language : Vocabulary and Transliteration -- Preface -- Acknowledgments -- Introduction -- Challenging the Philosophical Presupposition : Gandhi's Unconventional Synthesis of Asceticism and Activism -- Gandhi's Alternative Paradigm : From Traditional Principles to New Political Purposes -- The Traditional Roots of Gandhi's Brahmacarya -- Gandhi's Unorthodox Brahmacarya : Reinterpreting Private Religious Practice for Public Service -- Gandhi's Embodiment of Legendary Heroes and Ascetics : Toward a Coherent Narrative for Nonviolent Activism -- Conclusion : Gandhi's Dynamic Synthesis of Renunciation and Social Action.
Includes bibliographical references (pages 271-280) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Gandhi, -- Mahatma, -- 1869-1948 -- Philosophy; Gandhi, -- Mahatma, -- 1869-1948 -- Religion; Gandhi, -- Mahatma, -- 1869-1948; Asceticism -- Hinduism; Celibacy -- Religious aspects -- Hinduism; Passive resistance; Nonviolence; Ascétisme -- Hindouisme; Résistance passive; Non-violence.; RELIGION -- Hinduism -- General; Asceticism -- Hinduism; Nonviolence; Passive resistance; Philosophy; Religion